2009
DOI: 10.1534/genetics.109.105486
|View full text |Cite
|
Sign up to set email alerts
|

A New Standard Genetic Map for the Laboratory Mouse

Abstract: Genetic maps provide a means to estimate the probability of the co-inheritance of linked loci as they are transmitted across generations in both experimental and natural populations. However, in the age of whole-genome sequences, physical distances measured in base pairs of DNA provide the standard coordinates for navigating the myriad features of genomes. Although genetic and physical maps are colinear, there are well-characterized and sometimes dramatic heterogeneities in the average frequency of meiotic rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
256
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 211 publications
(285 citation statements)
references
References 41 publications
28
256
0
1
Order By: Relevance
“…The introgressed region of the B6.D2 Csnk1e line spanned 78-86.8 Mb whereas for the D2.B6 Csnk1e line spanned 78.7-81.6 Mb. The latter region was estimated to be B0.56 cM (Cox et al, 2009). As expected, the results of the SNP array confirmed that each congenic line contained o1% RH.…”
Section: Reciprocal Congenic Regionssupporting
confidence: 82%
“…The introgressed region of the B6.D2 Csnk1e line spanned 78-86.8 Mb whereas for the D2.B6 Csnk1e line spanned 78.7-81.6 Mb. The latter region was estimated to be B0.56 cM (Cox et al, 2009). As expected, the results of the SNP array confirmed that each congenic line contained o1% RH.…”
Section: Reciprocal Congenic Regionssupporting
confidence: 82%
“…The marker map file was created using marker position data provided by GeneSeek. Marker positions in National Center for Biotechnology Information Build 37 were converted to genetic distances in sex-averaged centimorgans using the Jackson Laboratory's Mouse Map Converter tool (http://cgd.jax.org/mousemapconverter/) (40,41). The genetic map of the markers used for analysis was plotted using the plot.map function in R/ qtl.…”
Section: Methodsmentioning
confidence: 99%
“…We used the genetic distance estimates from the reference panel described in Cox et al (2009). These estimates were retrieved from the Mouse Map Converter hosted at Jackson Laboratories (http://cgd.jax.org/mousemapconverter).…”
Section: Genotype Imputationmentioning
confidence: 99%